Day-to-day variation in adolescent food insecurity. (June 2023) - Gassman-Pines, Anna; Bellows, Laura; Copeland, William E.; Hoyle, Rick H.; Odgers, Candice L.
Highlights: Food insecurity among adolescents is not static but varies from day to day. This daily variation is greater for economically disadvantaged youth. Black adolescents also had higher average food insecurity and more daily variability. Abstract: This study examined differences in both average and variability in daily adolescent food insecurity, by adolescents' levels of economic disadvantage and race/ethnicity. We used data from a 14-day ecological momentary assessment of 395 adolescents enrolled in public schools in North Carolina. Each evening, adolescents were asked questions about that day's food insecurity. Economically disadvantaged adolescents reported both higher average food insecurity and more day-to-day variability in food insecurity than non-economically disadvantaged adolescents. Controlling for economic disadvantage, Black adolescents also experienced both higher average food insecurity and more variability from day to day than White or Hispanic adolescents. For those receiving Supplemental Nutrition Assistance Program (SNAP) benefits, daily food insecurity was higher in the second half of the month after SNAP transfer than in the beginning of the month. Food insecurity among adolescents is not static but varies from day to day. This daily variation is greater for economically disadvantaged youth.